optimasi penggunaan spent coffee grounds (scg) sebagai pupuk organik pada tanaman selada (lactuca sativa l) - Denia Handayani (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2025)
Spent coffee grounds (SCG) are organic waste materials that have the potential to be processed into fertilizer to support sustainable agriculture. The aim of this research is to optimize the use of SCG in lettuce plants (Lactuca sativa) through two forms of fertilizer, namely solid and liquid, with three variations of doses each: 50, 100, and 150 g/ml. There are seven treatments in the study, consisting of one control (without SCG), three solid fertilizer treatments (P1, P2, P3), and three liquid fertilizer treatments (P4, P5, P6). Observations were made on plant growth over a period of 45 days. The results show that the best treatment was in the control group, while the less optimal treatment was found in P6 (liquid fertilizer at a dosage of 150 ml). This indicates that SCG, especially in liquid form at high doses, has not been optimally used as fertilizer for lettuce plants. Further formulation and processing are needed so that SCG can be used effectively without compromising plant growth quality..
Reuploud file repositori 13 Apr 2026_Firli_tata
Keywords: EM4; lettuce; SCG (spent coffee grounds)